2020
DOI: 10.32892/jmri.212
|View full text |Cite
|
Sign up to set email alerts
|

Blacks’ Diminished Health Returns of Educational Attainment: Health and Retirement Study

Abstract: Background: Education level reduces the risk of health problems such as poor self-rated health (SRH), high body mass index (BMI), and depressive symptoms (DS). Marginalization – related Diminished Returns (MDRs), however, refer to smaller health benefits of socioeconomic status (SES) indicators particularly educational attainment for the members of racial minority groups such as non-Hispanic Blacks compared to the majority group (non-Hispanic Whites). It is not known, however, if MDRs also hold for middle-age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 85 publications
(131 reference statements)
2
5
0
Order By: Relevance
“…Nevertheless, findings showed weaker effects of educational attainment on the functional limitations of Black adults than White adults, suggesting that their effects were racially stratified. Findings align with previous studies that reported lower returns for Black Americans from SES in terms of self-rated health, chronic disease, body mass index, and activity limitations (Assari, 2020; Braveman et al, 2010; Holmes & Zajacova, 2014; Hudson et al, 2013). These findings reflect detrimental health impacts of overtly racist practices against Black Americans before the Civil Rights Act, such as redlining, segregated schools, and the discriminatory labor market (Hout, 1984).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Nevertheless, findings showed weaker effects of educational attainment on the functional limitations of Black adults than White adults, suggesting that their effects were racially stratified. Findings align with previous studies that reported lower returns for Black Americans from SES in terms of self-rated health, chronic disease, body mass index, and activity limitations (Assari, 2020; Braveman et al, 2010; Holmes & Zajacova, 2014; Hudson et al, 2013). These findings reflect detrimental health impacts of overtly racist practices against Black Americans before the Civil Rights Act, such as redlining, segregated schools, and the discriminatory labor market (Hout, 1984).…”
Section: Discussionsupporting
confidence: 89%
“…With a few exceptions (e.g., Barnes et al, 2011; Ostrove et al, 1999), a growing number of studies have established racial stratification in the education-health gradient. Using both regional (e.g., Turner et al, 2017) and national data (e.g., Holmes & Zajacova, 2014), these studies have documented that education has a lesser impact on self-rated health, chronic diseases, body mass index, and activity limitations for Black Americans than White Americans (Assari, 2020; Braveman et al, 2010; Cummings & Jackson, 2008; Farmer & Ferraro, 2005). However, little attention has been paid to the role of intersecting early-life selection mechanisms (i.e., selection bias or confounding bias introduced by observed common causes such as childhood socioeconomic status (SES) that impact both educational attainment and health) in constituting racial stratification in the effects of education on later-life health.…”
Section: Introductionmentioning
confidence: 99%
“…7,17 Similar to a prior analysis using the Health and Retirement Study data examining the MDRs of education against self-rated health, BMI, and depressive symptoms, no differences were found for the protective effects of higher education against self-rated health and depressive symptoms for Black or White adults. 30 One potential explanation for our findings is that the MDRs hypothesis has a larger impact at the higher end of the SES distribution. Recent findings from Spikes et.…”
Section: Discussionmentioning
confidence: 79%
“…Ample evidence shows diminished returns for economic/class achievement for Black people. Compared to Whites, increased education among Black people is not associated with better mental or physical health, including self-reported health or depressive symptoms (Assari, 2020;Assari et al, 2018a), emotional well-being (Assari et al, 2018b), obesity (Assari, 2018b), or chronic obstructive pulmonary disease (Assari et al, 2019a). Education was also not a protective factor against negative health behaviors, including smoking (Assari and Mistry, 2018) or alcohol binge drinking (Assari et al, 2019b).…”
Section: Mdr and Psychedelicsmentioning
confidence: 99%
“…Most recently, researchers have begun to analyze the potential of psychedelics to positively impact the health of people of color who, compared to their White counterparts, continue to suffer both mentally and psychologically with higher rates of all-cause morbidity, which results in a lower life expectancy (Assari, 2017a, 2018a, 2020; Assari, Lapeyrouse, et al, 2018; Assari and Mistry, 2018; Assari, Preiser, et al, 2018b; Assari, Chalian, et al, 2019; Assari, Farokhnia, et al, 2019). But results are proving mixed.…”
Section: Introductionmentioning
confidence: 99%